Saúde mental masculina: prevalência e vulnerabilidades aos transtornos mentais comuns nos contextos rural e urbano - Bezerra, Edilane Nunes Régis (2017)
Psychic illness, highlighting Common Mental Disorders (CMD), one of bigest issues menking is facing actually, from non-psychotic nature. Those disorders involves a sinals set and related symptoms, mainly, to somatic problems and depressive and anxiety symptons generally related to life conditions and occupational structure. So, our goal is to analyse the vulnerabilities aspects on common mental disorders in Paraíba’s men, comparing urban and rural contexts. There were realized two empiric studies. The first is a quantitative epidemiological research wich its objective was estimate the prevalence of common mental disorders in capital and rural cities’ on men from Paraíba, associated to social economic factors, life style, search for treatment and mental health. In a sample of 432 men (160 linving in capital and 272 living in rural cities), from 21 to 59 years-old age group, were applyed a set of instruments: SRQ-20; Life Style, Acess and Health Atendance, Mental Health and Social-Demographic Questionnaries, which results were evaluated by descriptive statistics, Prevalence ratio, association (chi-square and test t) and multivariate. The CMD prevalence found among men from urban context was 46,3% and 18,4% from rural. It was observed the association between CMD presence and the age group (X2=9,183; p=0,01), with higher prevalence on yougest age group (44%), decreasing during life course (40% on group between 30 and 49 years-old and 15% on group above 50 years-old). The schoolarity association (X2=11,182; p=0,01) points to prevalence increase with schoolarity (basic: 29%; high school: 38%; university: 30%); so, we can deduce, given sample’s low Family income, that suffering can come from Family income increasing abstance after increasing the schoolarity level. At last, there was the association of CMD presence with marital status (X2=11,755; p=0,008), with bigger difference between singles (43%). The second study, qualitative, had as objective to analyse – from the participants description, which vulnerabilities elements (individuals, socials and programmatic) to CMD are presents on men’s lives from cities rurals and urbans. There were 07 men from rural context and 16 from urban context participating, with ages from 21 to 59 years-old, it was utilized individual enterviews analyzed through themactic categorial technique. Thematic categorization allowed obtaining three thematic classes: the first named “Male Suffering Contexts” refered to suffering individual aspects and involved seven analysing categories, a) Symptomatology; b) Main motives to getting ill; c) Illness consequences; d) Selfcare practices; e) Health care; f) Metal Health Care; g) Social support net. In second thematic class, named “Male Psychic Suffering Experiences”, had made refference to suffering social and intersubjetives aspects involved four analysis categories: a) Marital Relations; b) Gender Relations; c) Labor factors which step in metal health; d) Rural and urban everyday. The third thematic class was named “Professionals more sensitive and humanized to male suffering”. The results allowed to conclude, in urban context, that the relation between individual, social and programatic aspects associated to urban violence, finantial issues, unemployment, marital issues, lack of perspective and professional grown, health issues (family and personal), work oveload, social isolation, contrinute to CMD vulnerability situations between men linving on urban context.